Desempenho agronômico, rendimento e qualidade das sementes de genótipos de trigo em resposta à época de semeadura - Viganó, Joselaine (2008)
Sowing period is highly important for the establishment and development of wheat culture. Owing to genotype and environment interaction the determination of sowing periods inherent to each region is mandatory. Current research evaluates the agronomic performance, yield and seeds physiological quality from wheat cultivars as a function of the sowing period. Field experiment was undertaken on the Experimental Farm of the Central Cooperative unit in Agricultural Research (Coodetec) in Palotina PR Brazil. Seeds physiological quality was undertaken at the Seed Technological Laboratory of the Applied Research Agriculture Nucleus (Nupagri) of the State University of Maringá (UEM), Maringá PR Brazil. Design consisted of randomized blocks with four repetitions during the 2006 and 2007 harvests, with six wheat cultivars (CD 104, CD 105, CD 108, CD 110, CD 111 and CD 114), sown during five periods (22/03, 07/04, 20/04, 04/05 and 18/05). Wheat ears, plant height, maturation, number of emerged plants per square meter, number of ears per square meter, number of grains per ear, grain mass per ear, mass of one thousand grains, layers, yield, hectoliter weight, first and finish germination count, classification of seedlings vigor, soil-less cold test, accelerated aging and electric conductivity were the evaluated factors. With the exception of the variable layers, data was submitted to set analysis. Results show that environmental condition among harvests was the factor that most affected maturation. Highest grain yield for the six wheat cultivars was obtained in the April sowing. Yield was related to the grain mass per ear and mass of one thousand grains. With exception of CD 104 (period 22/03 of 2006), early and the later of the sowing period, had not contributed for the increase of the yield of the studied genotypes. Sowing period had only a slight influence on germination percentage of cultivars. Cultivars CD 105 and CD 108 less had been influenced by the sowing period when evaluated by means of the tests germination and vigor. Periods 22/03 and 07/04 had not been adjusted to the genotypes CD 110, CD 111 and CD 114 how much to the bulk density and to the physiological quality by means of the tests of germination, first counting, classification of seedlings vigor and accelerated aging.